2009
DOI: 10.1371/journal.ppat.1000591
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Abrasion Scanning Electron Microscopy Reveals Surface-Connected Tubular Conduits in HIV-Infected Macrophages

Abstract: HIV-1-containing internal compartments are readily detected in images of thin sections from infected cells using conventional transmission electron microscopy, but the origin, connectivity, and 3D distribution of these compartments has remained controversial. Here, we report the 3D distribution of viruses in HIV-1-infected primary human macrophages using cryo-electron tomography and ion-abrasion scanning electron microscopy (IA-SEM), a recently developed approach for nanoscale 3D imaging of whole cells. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(154 citation statements)
references
References 30 publications
11
143
0
Order By: Relevance
“…3A, Fig. S2, and Movie S3), similar to those recently described in HIV-infected macrophages (22,23). At the synapse, cell-cell contact involves extensive interdigitation of the respective cell membranes, with filopodial extensions from the T cell penetrating into the recesses of the virion-rich surface folds of the dendritic cell.…”
Section: Resultssupporting
confidence: 76%
“…3A, Fig. S2, and Movie S3), similar to those recently described in HIV-infected macrophages (22,23). At the synapse, cell-cell contact involves extensive interdigitation of the respective cell membranes, with filopodial extensions from the T cell penetrating into the recesses of the virion-rich surface folds of the dendritic cell.…”
Section: Resultssupporting
confidence: 76%
“…In addition, it has been reported that macrophages harbor infectious HIV-1 over a long period of time (39) and that the virus has evolved strategies to inhibit the acidification of endosomal compartments, thereby preventing viral degradation (21). However, the formation and dynamics of the VCCs are still elusive, and it has also been proposed that these correspond to internally sequestered plasma membrane domains, which are connected to the cell surface via small microchannels (4,9,22,45).…”
Section: Acrophages Are Important Hiv-1 Target Cells In Vivomentioning
confidence: 99%
“…25 Sections with nominal thicknesses of 100 nm and 175 nm were prepared using a Leica Ultracut microtome and imaged in a Tecnai 12 electron microscope (FEI Company) operated at 120 kV, and equipped with a 4K ϫ 4K Gatan charge-coupled device. For tomography, images were recorded over an angular range of Ϯ 70 degrees, and reconstructed to obtain a 3D volume using weighted back projection as implemented in the image processing package IMOD.…”
Section: Electron Tomographymentioning
confidence: 99%
“…Because DC-SIGN has previously been identified as a factor promoting DC-T cell infectious synapse formation, 6,25 we investigated whether HIV-1 could trigger a signaling program that induces actin-based protrusions at the surface of DCs, thereby facilitating an anterograde viral transfer from DCs to CD4 ϩ T cells across infectious synapses. Our results demonstrate a 2-step model for HIV-1 transfer from immature DCs to T cells that involves HIV-1 env engagement of the DC-SIGN receptor, leading to Cdc42 activation and formation of membrane extensions, followed by the Cdc42-dependent transfer of virus to the T-cell.…”
Section: Introductionmentioning
confidence: 99%